The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/1982083
|View full text |Cite
|
Sign up to set email alerts
|

Association of Salivary Statherin, Calcium, and Proline-Rich Proteins on Oral Hygiene: A Cross-Sectional Study

Abstract: Background. Saliva, as a complex biofluid, plays a pivotal role in maintaining oral health and tooth integrity. There has been inconsistent data available on the relationship between salivary parameters and oral health. This study aims to investigate the association between salivary statherin, acidic proline-rich proteins (aPRP), and calcium with oral hygiene status. Methods. One hundred and eighty-eight healthy subjects aged between 18 and 50 years with varying oral hygiene status who gave consent to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Four included studies were conducted in India [ 15 , 16 , 17 , 18 ], three studies in Poland [ 19 , 20 , 21 ], two in Brazil [ 22 , 23 ] and one multinational [ 24 ]. Each of the remaining seven studies were performed in China [ 25 ], Kosovo [ 26 ], Chile [ 27 ], Romania [ 28 ], Colombia [ 29 ], Egypt [ 30 ], Malaysia [ 31 ] and Iraq [ 32 ]. All the included studies were conducted within the last 12 years, but the majority were conducted between 2015 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four included studies were conducted in India [ 15 , 16 , 17 , 18 ], three studies in Poland [ 19 , 20 , 21 ], two in Brazil [ 22 , 23 ] and one multinational [ 24 ]. Each of the remaining seven studies were performed in China [ 25 ], Kosovo [ 26 ], Chile [ 27 ], Romania [ 28 ], Colombia [ 29 ], Egypt [ 30 ], Malaysia [ 31 ] and Iraq [ 32 ]. All the included studies were conducted within the last 12 years, but the majority were conducted between 2015 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The articles also presented a significant collective sample size. A total of 1454 participants, of both adults and children of both genders, were recruited in the 18 included studies, with the least sample size reported for a single study being 24 participants [ 29 ] and the largest being 188 participants [ 31 ]. Nevertheless, of the full sample size, 936 were minors aged between 2 years and 18 years which was reported in 11 of the included sources.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary proteins play an essential role in maintaining a healthy oral environment. Notably, salivary proteins such as basic proline-rich proteins (bPRPs), acidic proline-rich proteins (aPRPs), histatins, cystatins, mucins, statherins, and amylase exhibit antimicrobial and/or antiviral properties and maintain oral lubricity and mineral composition of dental surfaces that collectively form a key cornerstone of oral immunity [ 3 ]. Many of these proteins directly or indirectly inhibit bacterial growth via disruption of their enzymes or manipulate bacterial adhesion mechanisms, therefore, affecting biofilm formation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%